Pramipexole for the treatment of early Parkinson''s disease. (July 2011) - Perez-Lloret, Santiago; Rey, Maríía Veróónica; Ratti, Luca; Rascol, Olivier
Pramipexole is a nonergolinic dopamine agonist, with high affinity for the D2 subfamily of dopamine receptors. Pramipexole is efficacious for the symptomatic treatment of early Parkinson''s Disease (PD) and its early use, before that of levodopa can delay the emergence of levodopa-related motor complication. Dosage should be increased gradually from a starting dose of 0.375 mg/day up to a maximum of 4.5 mg/day in equally divided doses taken three times per day with pramipexole immediate-release or equivalent daily dosages once-daily with pramipexole extended-release. Pramipexole can also improve depressive symptoms and possibly health-related quality of life in PD. Nonetheless, its use is not devoid of tolerability problems. While peripheral adverse drug reactions, such as nausea, vomiting or orthostatic hypotension, can be effectively treated and usually pose few problems to most patients, neuropsychiatric events can seriously limit the use of pramipexole in some cases. Indeed, excessive daytime somnolence, impulse-control disorders, hallucinations or delusions can severely affect patients, causing important personal or social handicap. Patients should be informed about the risk of such neuropsychiatric complications and their presence should be actively detected at each consultation. More effort will have to be put into further studying the risk––benefit ratio of pramipexole and other dopamine agonists in the treatment of early PD.